Determination of spillway capacity of proposed bengoh dam - John Gary, J. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The aim of the study is to determine the spillway capacity of proposed Bengoh dam. The proposed Bengoh dam is located 43 km away from Kuching city. The purpose of the construction of Bengoh dam is to supply more raw water supply to Batu Kitang Water Treatment Plant due to increase in water demand in Kuching area. The geography and hydrology location of Sg. Bengoh make it suitable to construct a dam in that location. The Bengoh dam’s spillway should be able to pass the peak outflow during the design flood in Sg. Bengoh. In this study, the determination of spillway capacity of proposed Bengoh dam is conducted by analyzing the design flood to produce the outflow hydrograph for the spillway. The determination of spillway capacity is very important in designing spillway structure. Sufficient design of spillway can avoid dam overtopping which may lead to destruction of the dam that can affect the environment and injury to human downstream of the dam.